2022
DOI: 10.3389/fpls.2022.1030620
|View full text |Cite
|
Sign up to set email alerts
|

Field application of silicon alleviates drought stress and improves water use efficiency in wheat

Abstract: Detrimental impacts of drought on crop yield have tripled in the last 50 years with climate models predicting that the frequency of such droughts will intensify in the future. Silicon (Si) accumulation, especially in Poaceae crops such as wheat (Triticum aestivum L.), may alleviate the adverse impacts of drought. We have very limited information, however, about whether Si supplementation could alleviate the impacts of drought under field conditions and no studies have specifically manipulated rainfall. Using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…hydroponics or greenhouses [12] and only few field studies were undertaken (e.g. [16]), precluding conclusions about the relevance of Si-mediated drought resistance for wild tropical seedlings. Particularly, the very low water potentials of droughted tropical soils [17] have not been reached.…”
Section: Introductionmentioning
confidence: 99%
“…hydroponics or greenhouses [12] and only few field studies were undertaken (e.g. [16]), precluding conclusions about the relevance of Si-mediated drought resistance for wild tropical seedlings. Particularly, the very low water potentials of droughted tropical soils [17] have not been reached.…”
Section: Introductionmentioning
confidence: 99%
“…It can increase plant C content through stimulating the formation of phytoliths, this way enhancing long-term C sequestration potential [ 11 ]. Hence Si treatment is expected to have a great potential to improve crop performance on marginal soils, and has been proposed as a large scale sustainable solution to counteract negative impacts of drought on crops [ 12 , 13 ]. However, despite multiple tests of individual mechanisms associated with crop response to Si treatments, an exhaustive assessment of the impacts of Si treatment on soil functioning and associated ecosystem services has to the best of our knowledge so far not been performed, especially in the context of climate adaptation of marginal soils.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, silicon-based fertilizers have received increasing attention for their ability to alleviate the adverse effects of drought stress in plants (Malik et al, 2021). It has been reported that silicon fertilizers can alleviate drought stress by improving the antioxidant defense systems and photosynthetic metabolism (Johnson et al, 2022;, maintaining intracellular homeostasis (Bhardwaj and Kapoor, 2021), tuning the auxin levels (Mir et al, 2022), and regulating the homeostasis of the oxidation of nitroso-compounds (Bhardwaj et al, 2022). The bioavailability of silicon fertilizers is less, however, NP-based silicon fertilizers were more likely to penetrate into the leaf cells and play a more direct function (Biju et al, 2021), leading to the usage of nanoparticles (NPs) could be an important approach to alleviate soil salt stress (Badawy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%